1992
DOI: 10.1002/bjs.1800790722
|View full text |Cite
|
Sign up to set email alerts
|

Bile duct stents in the management of hepatolithiasis with long-segment intrahepatic biliary strictures

Abstract: Biliary stricture represents a challenging problem in the treatment of hepatolithiasis because of its association with treatment failure and stone recurrence. The long-segment type of stricture is difficult to manage and is likely to recur. To investigate the necessity for biliary stenting after balloon dilatation therapy, 20 consecutive patients with long-segment strictures who had 22 stents (group 1) were compared with ten patients who refused stenting (group 2). The long-segment strictures in group 1 were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…3,4,15 It develops biliary strictures, bile duct wall thickness, bile retention, and suppurative cholangitis. 3,4 It is the main cause of residual and recurrent stones, [1][2][3][5][6][7]15 which are the most difficult problems in hepatolithiasis treatments. [1][2][3] A number of hepatolithiasis treatment options, including surgical procedures like choledochotomy, hepaticojejunostomy, hepatectomy, and papilloplasty, have been performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,4,15 It develops biliary strictures, bile duct wall thickness, bile retention, and suppurative cholangitis. 3,4 It is the main cause of residual and recurrent stones, [1][2][3][5][6][7]15 which are the most difficult problems in hepatolithiasis treatments. [1][2][3] A number of hepatolithiasis treatment options, including surgical procedures like choledochotomy, hepaticojejunostomy, hepatectomy, and papilloplasty, have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]16,20,21 As well, the restenosis rate after biliary strictures had been successfully dilated using the balloon dilatation method was 24% to 58% during a follow-up period of 3 to 7.5 years. [5][6][7]18,19,22 Thus, because these kinds of treatment options have failed to significantly reduce the rates of the residual and recurrent stones following them, some additional or supportive strategies have been required for reducing those rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cox proportional hazards model indicated that a liver resection range less than the range of stone distribution was the only independent risk factor associated with stone recurrence in this study. A liver resection range less than the range of stone distribution may leave bile duct stricture, which is a key predisposing factor for stone recurrence [9][10][11] . There is reluctance among some surgeons to perform bilateral liver resection for bilobar stones because of the associated surgical risks.…”
Section: Discussionmentioning
confidence: 99%